VULNERABILITY AND HUMAN RIGHTS: TACKLING SEXUAL AND GENDER-BASED VIOLENCE AGAINST MIGRANTS AND ENHANCING SUPPORT TO VICTIMS (Security Dialogues, 2024)
This paper seeks to improve understanding of the risks and types of sexual and gender-based violence faced by migrants, as well as ways of providing protection and assistance within the mixed migration context in Bosnia and Herzegovina. The Center for Disease Control and Prevention states that over half of women and almost 1 in 3 men worldwide have experienced sexual violence involving physical contact during their lifetimes. Even though the prevalence of sexual violence is high, its exact scope is unknown due to its vast underreporting. Sexual violence against people on the move is widespread. Regardless of age and gender, this population is highly vulnerable to becoming victims of sexual and gender-based violence during their journey toward the desired destination. How the proper activities aimed to prevent and treat the consequences of sexual and gender-based violence in the humanitarian context are set up in Bosnia and Herzegovina and what kind of services are provided to victims will be discussed within the paper. How important the role of humanitarianworkers is, their understanding of sexual and gender-based violence, and their readiness to provide adequate care, recognize the types of sexual violence, and use all the benefits of the existing referral pathway properly will also be broadly explored.
Keywords: human rights, migration, sexual violence, gender-based violence, Bosnia and Herzegovina